URGENSI SERTIFIKASI HALAL PADA MAKANAN - Hasibuan, zulfan Efendi (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
Food is a human need for survival. but in Islamic law, it is ordered to consume halal and good food. Along with the changes and developments of the times, there are many foods that have doubts about their halalness, based on their processed ingredients and production methods. As a solution, MUI issued a fatwa so that every food traded must have a halal certificate. Some people are happy with the MUI fatwa, but there are also those who are against it.